Thermodynamics performance and heat transfer analysis of parabolic trough collector in solar power plant / Omid Afshar - Omid , Afshar (2013)
Today, solar energy can play a vital role in the world. Parabolic trough collector is one type of solar devices that play an important role in the power system. The main components of parabolic trough collector are curve mirror and receiver system. Iran is one of the potential countries that use parabolic trough power plant system. In this research thermodynamics performance like exergy and thermal efficiency will be considered on the first, tenth, fifteenth, twentieth, twenty-fifth and thirtieth of September. Iran will be considered as a case study in whole time. Then, heat transfer in different parts of receiver system will be analyzed at 250˚C. Based on some experimental tools, temperature and mass flow rate and solar parameter, can be estimated when it comes to thermodynamics and heat transfer values. The result shows that the value of exergy and thermal efficiency on the first of September is the highest. Second law efficiency on the first of September at 12 noon is around 10% and the value of exergy at that time is approximately 15.5kJ/kg in collector system. The value of convection heat transfer between the heat transfer fluid and the receiver pipe was around 15.5kW in 250˚C.